In vitro maturation impacts cumulus–oocyte complex metabolism and stress in cattle. Issue 6 (December 2017) - del Collado, Maite; da Silveira, Juliano C; Oliveira, Marcelo L F; Alves, Bárbara M S M; Simas, Rosineide C; Godoy, Adriana T; Coelho, Mirela B; Marques, Lygia A; Carriero, Mateus M; Nogueira, Marcelo F G; Eberlin, Marcos N; Silva, Luciano A; et al.
Abstract : The influence of in vitro maturation (IVM) in oocytes is still not totally understood. The aim of this study was to determine the influence of IVM on the metabolism and homeostasis of bovine cumulus-oocyte complexes. In the present study, we demonstrated that IVM leads to accumulation of neutral lipids associated with differential levels of the mono-, di- and triacylglycerols in both cumulus cells and oocytes. We observed that in vitro -matured oocytes exhibited decreased glutathione and reactive oxygen species levels and a lower ATP/ADP ratio when compared to in vivo -matured oocytes, with no significant differences in metabolism and stress-related mRNA or miRNA levels. Moreover, in addition to an increase in lipids in in vitro -matured cumulus cells, fatty acid synthesis and accumulation as well as glycolysis pathway genes were upregulated, whereas those affiliated with the β-oxidation pathway were decreased. Our gene expression data in cumulus cells suggest the disruption of endoplasmic reticulum stress, apoptosis and cellular stress response pathways during IVM. Furthermore, a total of 19 miRNAs were significantly altered by the maturation process in cumulus cells. These results indicate some new negative influences of the in vitro system in cumulus-oocyte complexes, demonstrating the occurrence of functional disruption in lipid metabolism and stress pathways and showing evidences suggesting the occurrence of altered mitochondrial activity and energy metabolism during IVM, with a massive dysregulation of the corresponding transcripts in the surrounding cumulus cells.